2012
DOI: 10.1080/10826068.2011.575910
|View full text |Cite
|
Sign up to set email alerts
|

BIOCATALYTIC ACTIVITY OF RECOMBINANT HUMAN Β-Mannosidase IMMOBILIZED ONTO MAGNETIC NANOPARTICLES FOR BIOPROCESS

Abstract: Recombinant human β-mannosidase (rhMANB) is an important glycosidase enzyme that degrades mannose-linked glycoproteins and mannan polysaccharides. rhMANB was purified and covalently immobilized onto magnetic nanoparticles. The immobilization of the enzyme was confirmed by Fourier-transform infrared spectroscopy (FTIR) and magnetic nanoparticles linked immunosorbent assay (MagLISA). Antibodies against rhMANB were raised, purified and characterized for MagLISA. The binding of rhMANB onto magnetic nanoparticles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In one such study, Khoshnevisan et al [12] reported cellulase loading to magnetic NP ratio of 0.033 which was very low. However, some other researchers have obtained a higher protein loading of 117 mg/g silica NP and 130 mg/g magnetic NP for cellulase and mannosidase respectively [36,37]. The enzyme loading depends on properties of enzyme, shape and size of NPs and ligand properties [42].…”
Section: Binding Confirmation Using Ftirmentioning
confidence: 98%
See 1 more Smart Citation
“…In one such study, Khoshnevisan et al [12] reported cellulase loading to magnetic NP ratio of 0.033 which was very low. However, some other researchers have obtained a higher protein loading of 117 mg/g silica NP and 130 mg/g magnetic NP for cellulase and mannosidase respectively [36,37]. The enzyme loading depends on properties of enzyme, shape and size of NPs and ligand properties [42].…”
Section: Binding Confirmation Using Ftirmentioning
confidence: 98%
“…Out of total 93 GHs identified, GH3 (22), GH 18 (14), GH 5 (7), GH10 (7) and GH 31 (6) Table 2. Various researchers have reported immobilization efficiencies ranging from 50-145% for different enzymes immobilized on various solid supports [12,[36][37][38]. Physical adsorption method is very simple and does not require any cross linker which makes this method less expensive.…”
Section: Analysis Of Extracellular Proteome Of a Niger Sh3mentioning
confidence: 99%
“…The number of amino groups attached onto MNP (less than 0.2 mm) was determined by using the molar extinction coefficient 6623 M À1 =cm. [27,28] The particles were stored at 4 C in water.…”
Section: Synthesis and Characterization Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…The dried pellets were processed for Fourier-transform infrared (FTIR) analysis as described. [27] Development of Anti-DOX and Anti-MTX Antibodies DOX was conjugated with bovine serum albumin (BSA) and oval albumin (OVA) by a two-step glutaraldehyde method. Similarly, MTX was also conjugated with bovine serum albumin (BSA) and oval albumin (OVA) by a two-step glutaraldehyde method.…”
Section: Fourier Transform Infrared (Ftir) Analysismentioning
confidence: 99%
See 1 more Smart Citation